Variable Upper Mantle Geochemical Processes Constrained From Independent Component Analysis of the Fizh Massif, Northern Oman Ophiolite - Yuto Miki; Eiichi Takazawa; Kenta Ueki; Tatsu Kuwatani (Geochemistry, Geophysics, Geosystems)
Abstract We statistically analyzed the whole‐rock compositions of peridotites in the Oman ophiolite using a multivariate statistical technique called independent component analysis (ICA) to better understand the processes within the ophiolitic mantle section that gave rise to the compositional variations, including partial melting, mantle–melt reactions, and peridotite–fluid interactions. We found that four independent geochemical components represent most of the geochemical variations in these peridotites. We compared the independent components with petrological and geological observations, such as the mineral abundances and compositions, whole‐rock major and trace element contents, and spatial distributions of these features. We found that the four independent components (IC1–4) correspond to four processes: anhydrous partial melting at a spreading ridge, slab‐derived fluid‐fluxed melting during subduction, serpentinization, and metasomatism, respectively. The compositional variations of peridotites in the Oman ophiolite are mainly due to two mantle processes: (a) anhydrous processes at a spreading ridge (partial melting); and (b) fluid–peridotite reactions during obduction and subduction, including metasomatism and serpentinization.